Models of the rapid post‐rift subsidence in the eastern Qiongdongnan Basin, South China Sea: implications for the development of the deep thermal anomaly. (25th January 2016) - Shi, Xiaobin; Jiang, Haiyan; Yang, Jun; Yang, Xiaoqiu; Xu, Hehua
Abstract: The Qiongdongnan Basin is one of the largest Cenozoic rifted basins on the northern passive margin of the South China Sea. It is well known that since the Late Miocene, approximately 10 Ma after the end of the syn‐rift phase, this basin has exhibited rapid thermal subsidence. However, detailed analysis reveals a two‐stage anomalous subsidence feature of the syn‐rift subsidence deficit and the well‐known rapid post‐rift subsidence after 10.5 Ma. Heat‐flow data show that heat flow in the central depression zone is 70–105 mW m −2, considerably higher than the heat flow (<70 mW m −2 ) on the northern shelf. In particular, there is a NE‐trending high heat‐flow zone of >85 mW m −2 in the eastern basin. We used a numerical model of coupled geothermal processes, lithosphere thinning and depositional processes to analyse the origin of the anomalous subsidence pattern. Numerical analysis of different cases shows that the stretching factor βs based on syn‐rift sequences is less than the observed crustal stretching factor βc, and if the lithosphere is thinned with βc during the syn‐rift phase (before 21 Ma), the present basement depth can be predicted fairly accurately. Further analysis does not support crustal thinning after 21 Ma, which indicates that the syn‐rift subsidence is in deficit compared with the predicted subsidence with the crustal stretching factor βc . The observed high heat flow in the central depression zone is caused by the heating of magmatic injection equivalently at approximately 3–5 Ma, which affected the eastern basin more than the western basin, and the Neogene magmatism might be fed by the deep thermal anomaly. Our results suggest that the causes of the syn‐rift subsidence deficit and rapid post‐rift subsidence might be related. The syn‐rift subsidence deficit might be caused by the dynamic support of the influx of warmer asthenosphere material and a small‐scale thermal upwelling beneath the study area, which might have been persisting for about 10 Ma during the early post‐rift phase, and the post‐rift rapid subsidence might be the result of losing the dynamic support with the decaying or moving away of the deep thermal source, and the rapid cooling of the asthenosphere. We concluded that the excess post‐rift subsidence occurs to compensate for the syn‐rift subsidence deficit, and the deep thermal anomaly might have affected the eastern Qiongdongnan Basin since the Late Oligocene.